TheEnvironmental Education approach into a Protected Area Turvo State Park, Derrubadas - Rio Grande do Sul, Brazil - Kuhnen, Claudia Felin Cerutti; Marcolan, Daliane Cristiane; Rocha, Marcelo Carvalho da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The Environmental Education (EE) is a tool capable of establish a close relation between the society and environment, by awareness about the environmental issues faced by the planet and by the developing of a critical sense related to the improper use of natural resources. The main goal of this work was to elaborate an approach of EE to be applied into a Protected Area (Turvo State Park, Derrubadas, RS, Brazil), based on its major attractive attributes as fauna, flora, historical factors and activities already developed at this spot. There was elaborated a proposal of nature trail by exploring local ecological traits of this ecosystem, as for instance, succession process, litter presence, characterization and stratification of Seasonal Deciduous Forest. Legal and conceptual aspects related to the EE were also discussed, which showed the need of implantation of this project.